GIS / Based approach using AHP method for selecting solid waste disposal site in Pokok Sena, Kedah / Nurul Natrah Jamaluddin - Jamaluddin, Nurul Natrah (2018)
Nowadays, solid waste management has become one of the most serious global environmental issues especially for developing countries like Malaysia. This is due to the population growth which has caused an increase in residential, commercial and infrastructure development. This negatively affects the environment and life quality. Despite the many facilities being provided by the municipal authorities to the communities, their solid waste management still did not achieve its objectives and satisfactory level. Thus, several territorial and legal factors in landfill siting should be considered in order to reduce negative impacts on the environment. The aim of this study is to evaluate present location of dumping site at JABI and propose a new location of dumping site in Pokok Sena, Kedah using Geographical Information System (GIS) and remote sensing (RS) technology. The types of data used are primary and secondary data. These includes Digital Elevation Model (DEM), satellite image, field observations and different geographical factors. Furthermore, these data were processed through several methods of GIS operation for evaluating present dumping site such as digitizing, buffering, overlaying, spatial analysis and Analytical Hierarchical Process (AHP). The result shows some suitable dumping sites successfully identified. This study proves that GIS and RS techniques are useful as important tools in selecting suitable sites for solid waste disposal. In addition, it serves as an effective identification of suitable solid waste disposal site that helps to solve the environmental issues. Keywords: solid waste, Geographical Information System (GIS), Analytical Hierarchical Process (AHP), remote sensing (RS), landfill siting